2015
DOI: 10.1590/2238-1031.jtl.v9n3a2
|View full text |Cite
|
Sign up to set email alerts
|

Micro-simulation based evaluation of Queue Jump Lane at isolated urban intersections: an experience in Kolkata

Abstract: Article Info AbstractKeywords: bus priority queue jump lane signalized intersection VISSIM urban IndiaPoor service quality is one of the major causes for declining share of buses in urban India. Improvement of bus travel time by implementing bus priority measures at intersections is well regarded as an effective instrument to improve bus service by reducing the travel time. However, only a few research works have been reported in the literature on bus priority strategies in Developing countries such as India. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The queue jump lane is a public transport priority measure that provides access to the intersection where one of the traffic lanes at an intersection ahead is a dedicated bus lane. Bus transport is not affected by the cars and thus the priority on traffic lights is easily manageable and public transport vehicles can pass through the intersection without stopping or even slowing down unnecessarily [10].…”
Section: Spatial Priority Measures and Queue Jump Lanementioning
confidence: 99%
“…The queue jump lane is a public transport priority measure that provides access to the intersection where one of the traffic lanes at an intersection ahead is a dedicated bus lane. Bus transport is not affected by the cars and thus the priority on traffic lights is easily manageable and public transport vehicles can pass through the intersection without stopping or even slowing down unnecessarily [10].…”
Section: Spatial Priority Measures and Queue Jump Lanementioning
confidence: 99%
“…QJ lanes have often been investigated via microsimulation. Maitra et al simulated three busy mixed-modal Kolkata intersections with and without QJ lanes, with the most extreme case reducing bus delay by 60 s ( 13 ). Truong et al showed that multiple consecutive QJ lanes can reduce bus delays by more than the sum of individual delay reductions, particularly at greater traffic volumes ( 14 ).…”
Section: Brief Review Of Treatment Options At Intersectionsmentioning
confidence: 99%
“…However, the effectiveness of such facilities for bus priority in the present context has not yet been adequately investigated. Only a few studies have been reported in literature, which are highly case-specific and based on traffic micro-simulation evaluation ( 30 , 31 ). The majority of the works related to bus QJL in other traffic environments have also been based on analytical and simulation modeling ( 32 34 ).…”
mentioning
confidence: 99%